One year after COVID: The challenges and outlook of Chinese micro and small enterprises - Kong, Tao; Yang, Xiaohan; Wang, Ranran; Cheng, Zijun; Zhang, Xiaobo (Center for Global Development, 2021)
The Center for Enterprise Research and the Institute of Social Science Survey at Peking University, in collaboration with Ant Group Research Institute, conducted a new wave of Online Survey of Micro- and Small-Enterprises (OSOME) in March 2021. OSOME is a continuing effort to gain a better understanding of China’s micro- and small- enterprises and self-employed businesses (MSEs) by conducting quarterly surveys on MSEs operating on the Alipay platform. The key findings of the first quarter 2021 survey are as follows: - After exposure to the COVID-19 pandemic for over a year, the operational status of micro-and-small enterprises has significantly improved. However, they still face serious cash flow constraints. - Cost increases, in some cases due to a price spike in raw materials, and weak demand remain two key challenges facing micro-and-small enterprises and self-employed businesses. In the residential sector, lack of demand is a general concern. - Compared with other forms of support, tax reduction is the most inclusive. The share of businesses that have received online loans has increased, while the average interest rate has slightly declined. - In general, respondents characterized the travel restrictions during Chinese New Year (February 2021) as harmful. In particular, businesses in the residential service sector and those located in smaller cities and rural areas seem to have been more negatively impacted. - In response to the COVID-19 shock, a higher percentage of newly established businesses adopted online sales and electronic information systems than those established earlier. - The confidence indices on market demand, production, and revenues for the next quarter have returned to positive territory, indicating an optimistic outlook. The employment index remained just below the normal level, suggesting subdued expectations of expanded employment in the next quarter.